The Effect of Leverage and Company Size on Company Value with Profitability as an Intervening Variable in Technology Sector Companies Listed on the IDX in 2021-2023 - Indah Maharani Putri; Rita Friyani; Ratih Kusumastuti (Harmoni Economics: International Journal of Economics and Accounting, 2025)
With profitability acting as an intervening variable, the purpose of this study is to ascertain how leverage and company size affect company value. This research employs a quantitative methodology. Purposive sampling was used to select 26 of the 47 technology businesses listed on the Indonesia Stock Exchange in 2021–2023, yielding 78 observations in total. Secondary data was gathered from company annual reports via the Indonesia Stock Exchange's official website and the websites of the pertinent businesses. Multiple linear analysis, traditional assumption testing, and hypothesis testing with SPSS V30 software are the data analytic techniques employed in this study. Documentation and literature research are the approaches used to gather data. The study's findings indicate that while company size has no bearing on profitability, leverage does. While debt and company size have little bearing on a company's value, profitability has an impact. Neither the impact of leverage on company value nor the impact of firm size on company value can be mediated by profitability.